2013
DOI: 10.1093/jrr/rrt127
|View full text |Cite
|
Sign up to set email alerts
|

Five-fraction CyberKnife radiotherapy for large brain metastases in critical areas: impact on the surrounding brain volumes circumscribed with a single dose equivalent of 14 Gy (V14) to avoid radiation necrosis

Abstract: The efficacy and toxicity of five-fraction CyberKnife radiotherapy were evaluated in patients with large brain metastases in critical areas. A total of 85 metastases in 78 patients, including tumors >30 cm3 (4 cm in diameter) were treated with five-fraction CyberKnife radiotherapy with a median marginal dose of 31 Gy at a median prescribed isodose of 58%. Changes in the neurological manifestations, local tumor control, and adverse effects were investigated after treatment. The surrounding brain volumes circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 26 publications
(37 reference statements)
1
60
0
Order By: Relevance
“…Some investigators recommend that even large tumours should be treated with limited (3-5) fractions in as short a period as possible to circumvent TDD. Although the data regarding the dosimetric factors relevant to radiation necrosis in FSRT are limited, as pre-viously mentioned, 4,5,12,13 increased fractionation is deemed imperative for large tumours to ensure the safety of treatment. 5,20 Non-consecutive delivery could also exploit the radiobiological advantage of FSRT for facilitating tumour reoxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some investigators recommend that even large tumours should be treated with limited (3-5) fractions in as short a period as possible to circumvent TDD. Although the data regarding the dosimetric factors relevant to radiation necrosis in FSRT are limited, as pre-viously mentioned, 4,5,12,13 increased fractionation is deemed imperative for large tumours to ensure the safety of treatment. 5,20 Non-consecutive delivery could also exploit the radiobiological advantage of FSRT for facilitating tumour reoxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data regarding the dosimetric factors relevant to radiation necrosis in FSRT are limited, as pre-viously mentioned, 4,5,12,13 increased fractionation is deemed imperative for large tumours to ensure the safety of treatment. 5,20 Non-consecutive delivery could also exploit the radiobiological advantage of FSRT for facilitating tumour reoxygenation. 20,21 The following provisions for the execution of FSRT for BM are recommended: expeditious commencement after planning image acquisition, volume-based selection of fractions (increased fraction number for larger tumours and vice versa) and unenhanced image surveillance during treatment for previously described situations, although the dose fractionation scheme should be finely tailored to each patient in consideration of other predictive factors affecting survival, such as the patient's Karnofsky performance status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient performance status and preoperative neurologic deficits reportedly improved in 57.1 and 70.6%, respectively. Another study [42] evaluating the efficacy and toxicity of 5-fraction CK radiotherapy in patients with large brain metastases in critical areas, demonstrated that a high rate of local tumor control and low rate of complications are achievable. They report a local tumor control rate of 92.9% during a median follow-up of 8 months and report that neurological manifestations improved in 50.9% of the patients.…”
Section: Clinical Studies -Hypofractionated Brain Treatmentsmentioning
confidence: 99%